Ultra‐wide bandgap Al0.1Ga0.9N double channel HEMT for RF applications. Issue 11 (15th August 2022) - Natarajan, Ramkumar; Parthasarathy, Eswaran; Murugapandiyan, Panneerselvam
Abstract: This article reports the performance analysis of gate field plate AlGaN dual channel high electron mobility transistor (HEMT). The proposed Al0.31 Ga0.69 N/Al0.1 Ga0.9 N/Al0.31 Ga0.69 N/Al0.1 Ga0.9 N heterostructures creates two quantum wells. Due to the strong coupling between two channels, device shown improved 2DEG (two‐dimensional electron gas), and enhanced carrier confinement. A distinct double‐hump feature is observed in both DC and RF characteristics of the proposed HEMT. For L G  = 0.8 μm, gate field plate ( L FP  = 0.5 μm), double channel HEMT shows the breakdown voltage of 695 V and F T / F MAX of 30/70 GHz. Moreover, the AlGaN double channel HEMT showed a ON‐state current density ( I DS ) of 0.7 A/mm, transconductance ( G m ) of 117 mS/mm, and lower noise figure. The proposed AlGaN channel HEMT in this work is suitable for future high‐power K‐band microwave applications.